How Are Patent Cases Resolved? An Empirical Examination of the Adjudication and Settlement of Patent Disputes - Jay P. Kesan; Gwendolyn G. Ball (Washington University Law Review, 2006)
From an institutional perspective, the patent system is a two-stage bargain. At the first stage, the U.S. Patent and Trademark Office (PTO) grants patent rights to inventors after conducting an examination of the prior art and of the patent application to determine whether the requirements for patentability are met. At the next stage, in order to enforce their issued patent rights, patentees have to resort to the federal courts with an action for patent infringement. This Article is organized as follows. Part II reviews the previous literature on patent litigation. Part III describes our methodology for collecting data on patent cases and classifying them according to the precise manner in which they were resolved. We then analyze the results and insights that we gain from a study of these case outcomes. Part IV presents our analysis of the costs of patent litigation, across all cases, for cases adjudicated through final judgments, and for cases with formal rulings of infringement or invalidity. In Part V, we present our conclusions.
Keywords: Patent infringement; Settlements; Copyright infringement; Injunctions